2012
DOI: 10.4238/2012.may.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and assessment of 23 microsatellite markers for parentage testing of Santa Inês hair sheep in Brazil

Abstract: ABSTRACT. Santa Inês is the most common hair sheep breed in Brazil and probably has the highest genetic diversity among sheep breeds in this country. Successful breeding programs for Brazilian sheep breeds are not common for various reasons, including a lack of control of parentage in the flocks. We developed an allele frequency database for 23 STR loci for the Santa Inês breed based on 285 animals sampled from five populations distributed across the central-western and north-eastern regions of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…The majority of the markers were highly polymorphic and generally in Hardy-Weinberg equilibrium, except for the marker DU223896 that showed the largest difference between observed and expected heterozygosity, and DU206192 for the highest null alleles frequency. The average number of alleles per marker (11.21) was considerably higher than that found in sheep populations in Bhutan (Dorji et al, 2010) and in Iran (Saberivand et al, 2011), whereas similar results were reported by Souza et al (2012) in Santa Inês sheep breed. Glowatzki-Mullis et al (2007) analyzed 10 different breeds with a 19-microsatellite multiplex (of which 10 are in common with our study) and found an average maximum of 7.79 alleles for Red Engadin sheep.…”
Section: Discussionmentioning
confidence: 39%
“…The majority of the markers were highly polymorphic and generally in Hardy-Weinberg equilibrium, except for the marker DU223896 that showed the largest difference between observed and expected heterozygosity, and DU206192 for the highest null alleles frequency. The average number of alleles per marker (11.21) was considerably higher than that found in sheep populations in Bhutan (Dorji et al, 2010) and in Iran (Saberivand et al, 2011), whereas similar results were reported by Souza et al (2012) in Santa Inês sheep breed. Glowatzki-Mullis et al (2007) analyzed 10 different breeds with a 19-microsatellite multiplex (of which 10 are in common with our study) and found an average maximum of 7.79 alleles for Red Engadin sheep.…”
Section: Discussionmentioning
confidence: 39%
“…Lowest heterozygosity and greatest inbreeding coefficient (F IS ) values exhibited by CRO population are shown in bold font. In general, the analyzed populations showed reasonably high allelic richness and heterozygosity values compared to some African (Soma et al, 2012;Kunene et al, 2014;Mukhongo et al, 2014), European (Salamon et al, 2014), Asian (Al-Barzinji et al, 2011;Blackburn et al, 2011b), and American (Blackburn, et al, 2011a;Souza et al, 2012;Ferreira et al, 2014) sheep breeds. The lowest values of AR and heterozygosity were observed in the crossbred population in which H O was notably lower than the H E (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…PCR were performed using a commercially available panel of eight microsatellite loci as previously described by Souza et al (2012) (CSRD247, HSC, OarAE129, MAF214, OarFCB304, OarCP49, SPS113, and D5S2). The reactions were performed using a multiplex fluorescent system, with the eight markers included in the same reaction.…”
Section: Microsatellite Locimentioning
confidence: 99%